POLYSEMIC ANALYSIS OF THE WORD 看 KÀN IN MANDARIN ANALISIS POLISEMI KATA 看 KÀN DALAM BAHASA MANDARIN - Jocelyn Paramita; Vivi Adryani Nasution (Jurnal Ilmiah Global Education, 2023)
Polysemy is a word that has more than one meaning and each meaning is related in one context and is also listed in the same entry in a dictionary. In Mandarin, the phenomenon of polysemy is also found, one of which is the word看 kàn. This study will describe the extended meaning of the word看 kàn and explain the relationship between the basic meaning and the extended meaning. Data were collected from the novel你是我的荣耀 nǐ shì wǒ de róng yào data source. The data is then analyzed by determining the classification of the meaning of the word 看 kàn and classified according to the type of meaning. Furthermore, this study explains the relationship between the basic meaning and the extended meaning of the word 看 kàn. From the data obtained through data sources, it is concluded that there are 6 extended meanings of the word看 kàn. The extended meanings found are: observe, consider, depend on, visit, diagnose; treat, take care of. Based on the results of the study, all the extended meanings of the word 看 kàn taken from the data source has semantic relationship with the basic meaning.